Assessing States’ Intimate Partner Violence Offender Treatment Standards using a Principles of Effective Intervention Framework - Richards, Tara N. (Journal of interpersonal violence, 2022)
Court-ordered treatment programs are a widely used response to intimate partner violence (IPV) and many states have developed standards to guide programs. The current study provides an update to Maiuro and Eberle?s. (2008) review of states? standards and extends the literature by using the principles of effective intervention (PEIs; i.e., risk, need, responsivity, treatment, and fidelity) as an organizational framework to examine standards. Findings showed that 84% of states had standards in 2020, compared to 88% in 2007, and extensive changes both within and across states? standards had occurred. Regarding the PEIs, in line with the risk principle most states mandated the use of risk assessments; inconsistent with the needs principle, few states used these assessments to classify clients into risk levels or inform individualized treatment. The majority of standards addressed the treatment principle by outlining a required structure and duration, but few attended to responsivity factors (e.g., identifying treatment modalities, attending to specific client factors). Regarding the fidelity principle, most standards outlined education or training requirements for staff and required periodic program reviews or audits, but few standards were evidenced-based and only about half required that programs collect data to measure effectiveness. Taken together, findings suggest that standards have continued to evolve and that the integration of PEIs into IPV treatment is only just beginning. Standards provide a rich opportunity for future researcher?practitioner partnerships in the field of IPV intervention.